Are You There, Law? It’s Me, Semen - Bernstein, Anita (Columbia Journal of Gender and Law, 2021)
Joining a conversation about menstruation and the law, this Essay interprets “law” to mean regulation––a source of burden, constraint, and interference justified by reason. The object of my regulatory agenda is a substance perceived by Western thinkers at least since Aristotle as the superior counterpart to menstrual fluid.1 Traditions that celebrate semen as vital or affirmative, while recoiling from and controlling the other gendered emission that hurts no one, get reality backward. Law as burden, constraint, and interference ought to regulate semen and leave menstrual fluid alone. Contrast the two substances. One of them started out with the potentially useful function of building a uterine lining. That possibility concluded, menstrual fluid is benign. The other effluvium started out with the potentially useful function of launching a pregnancy. Pregnancy is a good thing when it is desired by the person who has to live with the bulk of pregnancy’s detriments. Along with its capacity to do an important job, semen causes quite the array of harms. A statute on point for this purpose, the Federal Hazardous Substances Act, regulates material that “may cause substantial personal injury or substantial illness during or as a proximate result of any customary or reasonably foreseeable handling or use.”2 Because semen “has the capacity to produce personal injury or illness to man through ingestion, inhalation, or absorption through any body surface,” it also aligns with the definition of “toxic” in the statute.3 Judges, policymakers, litigants, and ordinary people can all learn from well-established legal labels to understand semen as a stark example of an externality. Nothing in this statute impedes the characterization I propose: The FHSA lists substances that lie outside its purview,4 and semen is not among them. Labeling, containment, and emergency protocols—splash protection, if you like—are the hazardous-substance safety impositions I would apply to semen.